Besarnya Kapasitas Kerja Screw Conveyor Untuk Mendorong Brondolan Dari Threser Menuju Digester pada PT X - Yanto Yanto; Gabriel Jafier Simanullang (JURNAL VOKASI TEKNIK, 2025)
Screw Conveyor is a mechanical system that has the functin of moving goods from one place to another place. Conveyor are widely used in industry for the transportation of goods in large quantities and continuously, one of wich is the screw conveyor. Screw conveyor are one of the most efficient and economical methods of moving bulk materials. Screw conveyor have been used generally to move industrial materials such as grains, fine coal, brondolan, and other materials. This tool consist of a knife that twists around an axis so that its shape resembles as a screw. This twisted blade is called a flight. Conveyor are made in lengths of 8-12 ft which can be combined to obtain a certain length. The diameter varies from 3-24 in. The speed of the screw conveyor in moving material will affect the capacity of the screw conveyor. From the evaluation results, the speed of the screw conveyor materials obtained was 0,163 m/s with a work capacity of the screw conveyor namely 17,36 tons/hour.